Pertunjukan Bedug Kerok sebagai Strategi Pengembangan Desa Wisata di Kampung Seni Yudha Asri - Samsul Fajri; Malarsih Malarsih; Hartono Hartono (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
Yudha Asri Art Village is the birthplace of Bedug Kerok. The aim of this study is to present and present the tourist village development strategy in the Yudha Asri Art Village through the Bedug Kerok show. Observations, interviews, documentation, and library surveys are data compilation techniques in qualitative descriptive research methods used in this study to discuss in detail phenomena raised in the research. The results of this research describe the strategy of development of tourist villages in the village of art Yudha Asri Village Mander, Bandung District, Serang District, Banten using the SWOT analysis matrix (Strength, Weakness, Opportunity, Treath).